Analyzing the determinants and challenges for transitioning conventional farmers towards agroecological practices in the centre region of Cameroon - Alphonse, Tiamgne Yanick; Garba, Hamamata Hawa; Nformi, Manu Ibrahim (International Journal of Sustainable Agricultural Research, 2024)
This research examined the socioeconomic and demographic characteristics of the respondents and sheds light on the farmers’ perceptions of agroecological practices and their transition. Agroecology is a sustainable development perspective for our rural communities. This study assessed the determinants and challenges for transitioning farmers from conventional agricultural practices to agroecological practices, focusing on farmers in the Centre region of Cameroon. The probability sampling method was employed to establish a representative study sample. By utilizing descriptive statistical analyses, frequencies observed among adopters and non-adopters were compared from the study. Key findings revealed significant socio-economic and demographic disparities between adopters and non-adopters. Gender, education level, farm size, and access to credit were identified as critical determinants of adoption. Men adopted agroecological practices (77%) more than women (23%). Adopters had higher levels of secondary (63%) and tertiary education (26%) compared to non-adopters. In addition, adopters had a large farm size (8.4 ha) compared to non-adopters (5 ha), and a higher percentage of adopters (40%) had access to credit facilities. This study highlighted varied perceptions among respondents, with risk aversion being a significant barrier to adoption. The study identified ignorance, financial constraint, and a lack of technical knowledge as major obstacles to widespread adoption. The study emphasized the substantial knowledge gap between adopters and non-adopters and highlighted the need for targeted interventions to address the challenges facing the widespread adoption of agroecological practices.